TRIM23 overexpression is a poor prognostic factor and contributes to carcinogenesis in colorectal cancer. Issue 10 (30th March 2020) - Han, Yudong; Tan, Ye; Zhao, Yuanyuan; Zhang, Yongchun; He, Xinjia; Yu, Li; Jiang, Haiping; Lu, Haijun; Tian, Haiying
Abstract: The tripartite motif (TRIM) family proteins play a great role in carcinogenesis. However, the expression pattern, prognostic value and biological functions of tripartite motif containing 23 (TRIM23) in colorectal cancer (CRC) are poorly understood. Here, we found that TRIM23 is up‐regulated and associated with tumour size, lymph node metastasis, American Joint Committee on Cancer (AJCC) stage and poor prognosis in CRC. Multivariate Cox regression analyses revealed that TRIM23 overexpression could be identified as an independent prognostic factor for CRC. TRIM23 could promote the proliferation of CRC cell in vitro and in vivo; additionally, TRIM23 depletion induced G1phase arrest. Gene set enrichment analysis (GSEA) revealed that P53 and cell cycle signalling pathway‐related genes were enriched in patients with high TRIM23 expression levels. We show in this study that TRIM23 physically binds to P53 and enhances the ubiquitination of P53, thereby promoting tumour proliferation. Thus, our data indicated that TRIM23 acts as an oncogene in colorectal carcinogenesis and may provide a novel therapeutic target for CRC management.